Wigner crystals for a planar, equimolar binary mixture of classical, charged particles - Antlanger, M.; Kahl, G. (Condensed Matter Physics, 2013)
We have investigated the ground state configurations of an equimolar, binary mixture of classical charged particles (with nominal charges Q₁ and Q₂) that condensate on a neutralizing plane. Using efficient Ewald summation techniques for the calculation of the ground state energies, we have identified the energetically most favorable ordered particle arrangements with the help of a highly reliable optimization tool based on ideas of evolutionary algorithms. Over a large range of charge ratios, q = Q₂ / Q₁, we identify six non-trivial ground states, some of which show a remarkable and unexpected structural complexity. For 0.59 \lesssim q < 1 the system undergoes a phase separation where the two charge species populate in a hexagonal arrangement spatially separated areas.